Relation between mutations in the 5′ UTR of ANKRD26 gene and inherited thrombocytopenia with predisposition to myeloid malignancies. An Egyptian study - Nahla Ibrahim Zidan; Doaa Metwally AbdElmonem; Haitham Mohamed Elsheikh; Elsayed Anany Metwally; Wesam AbdElmonem Mokhtar; Gamal Mohamed Osman (Platelets, 2021)
Inherited thrombocytopenias are a heterogeneous group of diseases characterized by a reduced number of platelets and a bleeding tendency that ranges from very mild to life threatening especially in surgery. Mutations in the 5′ untranslated region (UTR) of Ankirin repeat domain 26 (ANKRD26) are responsible for autosomal-dominant form of thrombocytopenia, that is known as ANKRD26-related thrombocytopenia (ANKRD26 RT), characterized by a moderate thrombocytopenia with mild propensity to bleeding and predisposition to hematological malignancies including AML and MDS. We included 90 unrelated patients with inherited thrombocytopenia. In addition, we investigated 45 patients with ITP. Peripheral blood and bone marrow samples were collected and examined and molecular detection of mutations in the 5︡ UTR of ANKRD26 gene was performed for all the patients. Also, screening of the mutation and development of myeloid malignancies in the extended series of the affected subjects was done. ANKRD26 mutations were identified in 10% of the patients with inherited thrombocytopenia. The most common types were c.128 G > A and c.127A>T, while no mutations were found in the ITP group. In those affected, the median number of platelets was 69 x109/L (43–106) with normal MPV in most of the patients (9.4–11.6). There was a statistically significant increase in the unexpected high frequency of myeloid malignancies in the extended series of the mutated subjects compared with the ITP group-extended series (P < .001). So, we can conclude that ANKRD26 RT is associated with increased risk for developing myeloid malignancies and ANKRD26 mutations can represent a valuable tool for making therapeutic decisions.